2013
DOI: 10.1364/oe.21.008177
|View full text |Cite
|
Sign up to set email alerts
|

Generation dynamics of the narrowband Yb-doped fiber laser

Abstract: We present direct real-time experimental measurements and numerical modeling of temporal and statistical properties for the Ytterbium-doped fiber laser with spectral bandwidth of ~2 GHz. The obtained results demonstrate nearly exponential probability density function for intensity fluctuations. A significant decrease below the Gaussian probability has been experimentally observed for intensity fluctuations having value more than 2.5 of average intensity that may be treated as indication of some mode correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…In general, temporal dynamics and statistical properties of quasi-CW fibre lasers are of great interest in recent years. There are experimental indications that intensity statistics in quasi-CW fibre lasers could be non-gaussian revealing increased probability of extreme events in RFLs 16,20 as well as non-Gaussian statistics in YDFL 21 . Moreover, recently it has been demonstrated that dark and grey solitons do really exist in the radiation of quasi-CW RFL operating in normal dispersion regime 22 .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…In general, temporal dynamics and statistical properties of quasi-CW fibre lasers are of great interest in recent years. There are experimental indications that intensity statistics in quasi-CW fibre lasers could be non-gaussian revealing increased probability of extreme events in RFLs 16,20 as well as non-Gaussian statistics in YDFL 21 . Moreover, recently it has been demonstrated that dark and grey solitons do really exist in the radiation of quasi-CW RFL operating in normal dispersion regime 22 .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…In a convenient experiment 13,19 laser radiation is registered by a photodetector and then transmitted to an oscilloscope. Since the photodetector has its limited input power range, high intensity peaks may be transmitted in a nonlinear way, but this impact can be omitted by a proper choice of used power range.…”
Section: Discussion Of Possible Instrumental Impactmentioning
confidence: 99%
“…As a result, the time dynamics of the RFL is complex with non-trivial statistical properties [8][9][10][11] . Other types of fiber lasers, for example, Ytterbium-doped fiber lasers, also reveal quasi-CW properties of the output radiation with non-gaussian statistics 12,13 . Possible mode correlations are reported recently in both YDFLs and short RFLs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear interaction of numerous modes lead to complicated temporal dynamics, for which statistical description is only possible. Non-trivial properties of radiation dynamics in fiber lasers with fiber Bragg gratings was observed in numerical simulations [2] and a number of experiments in different fiber laser types [3,4]. It was shown, that probability density function (PDF) has non-exponential shape, what indicates presence of spectral correlations.…”
Section: Introductionmentioning
confidence: 97%